Corrosion of engineering ceramic materials by molten iron Part II: Alumina. (August 2016) - Hnatko, M.; Tatarková, M.; Galusková, D.; Sedláček, J.; Bystrický, R.; Lenčéš, Z.; Šajgalík, P.
Highlights: The corrosion resistance of sintered Al2 O3 ceramics by molten iron at 1600 °C in N2 atmosphere has been investigated. The corundum material sintered without any sintering additives exhibited the higher corrosion resistance. The strength retention of Al2 O3 -A material after the corrosion tests in the molten Fe was around 53%. Chemical attack of molten iron with anorthite phase results in formation of silicides and a layer of hibonite. The strength retention of Al2 O3 -AH after the corrosion tests was around 47% of the initial value. Abstract: The corrosion resistance of two different polycrystalline materials based on the alumina (with and without sintering additives) in molten iron at 1600 °C has been investigated. The corundum without sintering additives was the most corrosive resistant among all investigated materials at studied conditions. Significant changes in microstructure has been detected in corundum prepared with CaO·5SiO2 (5 wt%) as a sintering additives due to the presence of anorthite Ca(Al2 Si2 O8 ) at the grain boundaries and triple points. In the present work the influence of exposure time on the residual strength of the polycrystalline materials has also been estimated.